PENERAPAN AKUNTANSI SYARIAH PADA BUDAYA DOI PAPPENRE DI BOLAPATAPPULOE - Syulistiani (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2024)
The word doi' pappenre itself is the same as panai money, but panai money is known in the Makassar area and the word doi' pappenre is known in the Luwu, Bone Sidrap, Pinrang areas. doi' pappenre is a doi' balance from a man to his future wife because in Bugis itself women are highly valued and held in high esteem, women are often identified as crowns where not just anyone can have them or even touch them, women are a symbol of the honor and dignity of the family